Classification of Acid Sulfate Soils of Peninsular Malaysia - Paramananthan, S.; Daud, Noordin (1986)
Acid sulfate soils form an important group of soils in Peninsular MaLaysia, particularly on the West Coast. These soils developed over marine, estuarine and brackish water deposits can be divided into two groups - the potential acid sulfate soils and the true acid sulfate soils using the definitions established in Soil Taxonomy. The classification of these soils in accordance to the Malaysian system is discussed. The Malaysian system though based on the concepts of Soil Taxonomy has been modified to suit local conditions. Two sequences of acid sulfate soils have been recognized in Peninsular Malaysia. A key to the identification of these acid sulfate soils is also presented in the paper.